2016
DOI: 10.1016/j.ultsonch.2016.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of power ultrasound on oxidation and structure of beef proteins during curing processing

Abstract: The aim of this study was to evaluate the effects of power ultrasound intensity (PUS, 2.39, 6.23, 11.32 and 20.96Wcm(-2)) and treatment time (30, 60, 90 and 120min) on the oxidation and structure of beef proteins during the brining procedure with 6% NaCl concentration. The investigation was conducted with an ultrasonic generator with the frequency of 20kHz and fresh beef at 48h after slaughter. Analysis of TBARS (Thiobarbituric acid reactive substances) contents showed that PUS treatment significantly increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
109
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(121 citation statements)
references
References 46 publications
7
109
0
5
Order By: Relevance
“…The change of the color parameters in meat samples can be generated by the effects of cavitation. This phenomenon during US treatment can induce free radicals and cause oxidation of lipid or protein [10,11]. Wolff et al [25] reported that the reactive oxygen species produced by lipid oxidation may modify or oxidize intracellular and membrane proteins in muscle.…”
Section: Effect Of Treatments On Physicochemical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The change of the color parameters in meat samples can be generated by the effects of cavitation. This phenomenon during US treatment can induce free radicals and cause oxidation of lipid or protein [10,11]. Wolff et al [25] reported that the reactive oxygen species produced by lipid oxidation may modify or oxidize intracellular and membrane proteins in muscle.…”
Section: Effect Of Treatments On Physicochemical Parametersmentioning
confidence: 99%
“…The violent implosion of cavities in solid surface may produce meat tissue damage and therefore affect the hardness, water holding capacity (WHC), and tenderization of the meat [5]. Likewise, US treatment can induce free radicals that are generated from water molecules as a result of cavitation and causing hydrolysis or oxidation of lipid [10,11], reactions which affected the color of the meat [12]. Regarding compression and expansion, these mechanisms may also affect the mass transfer and the structure of the meat.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 This additional buffer aims to protect proteins from denaturation due to heat produced by ultrasonic sound vibrations. 21 The analysis of the crude protein of S. mutans and S sanguis biofilms was performed to determine the protein profiles of S. mutans and S sanguis biofilms based on their molecular weight. The protein profiles of their biofilms depicted all the constituent proteins of S. mutans and S. sanguis biofilms.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, results of the protein profile analysis of S. sanguis biofilms using 12% SDS-PAGE showed that there were 15 bands, each of which molecular weight was 130, 85, 65, 61, 48, 46, 40, 37, 29, 25,23,21,17,15, and 12 kDa. And, results …”
mentioning
confidence: 99%
“…Kang et al [94] investigated treatment time versus ultrasonic power in an attempt to examine the oxidation of beef proteins. ey determined that sonicating beef under varying treatment conditions greatly increased the amount of lipid oxidation compared to static brining.…”
Section: Chemical Food Safetymentioning
confidence: 99%